Answer:
A) y = 4x - 1
Step-by-step explanation:
y = mx + b
y = 4x + b
7 = 4(2) + b
7 = 8 + b
-1 = b
y = 4x - 1
Step-by-step explanation:
From this figure TUW+WUV=TUV ; (5x+3)+(10x-5)=17x-16 so 15x-2=17x-16 ;14=2x therefore x=7
then substitute x on it.
TUW=5x+3=5(7)+3=35+3=38
WUV=10x-5=10(7)-5=70-5=65
TUV=17x-16=17(7)-16=119-16=103
Let the three odd integers be x - 2, x and x + 2
x - 2 + x = 3(x + 2) + 7
2x - 2 = 3x + 6 + 7
2x - 2 = 3x + 13
3x - 2x = -2 - 13
x = -15
The three consecutive odd integers are -17, -15 and -13.
Use a system of equations:
For his trip on the way there:
D = 7*s
For his trip on the way home you have:
D = 5*(s+18)
use substitution to solve